Influence of Perceived Benefits, Perceived Ease of Use, And Perceived Security On The Decision To Use The Indonesian Standard Quick Response Code (QRIS) Through Microenterprise Trust In Surabaya City - Afrianti, Nadya Mei; Arimbawa, I Gede; Artaya, I Putu; Baktiono, Agus (LPPM of NAROTAMA UNIVERSITY, 2025)
Objective: This study aims to analyze the influence of Perceived Benefits, perceived ease of use, and Perceived Security on the Decision to use the Indonesian Standard Quick Response Code (QRIS) among microenterprises in Surabaya City. Design/methodology/approach: This research was conducted to analyze whether there is an influence between independent and dependent variables. The method in this research uses quantitative methods, and in the analysis method using path analysis (Path Analysis), the population in this research is a micro enterprise in Surabaya City with a sample study as many as 100 respondents. Findings: The results of the study show that there is a significant influence of the variables of perceived benefits, ease of use, and security on the trust of micro-enterprise in the city of Surabaya, and there is a significant influence on the use of the Quick Response Code Indonesian Standard (QRIS) for micro enterprise in the city of Surabaya. Research limitations/implications: This research was only conducted in Surabaya City, especially in micro-enterprises as QRIS merchants. It is expected that further research can expand the independent variables of the research as well as the scope of other larger business places, and expand the location of the research area.